1997
DOI: 10.1002/eji.1830271118
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and the immunomodulation of experimental allergic encephalomyelitis

Abstract: Previous studies examining the effect of nitric oxide synthase (NOS) inhibition on the course of experimental allergic encephalomyelitis (EAE) have yielded conflicting results. This may relate to the use of nonspecific inhibitors and to differences between active and adoptive EAE. We examined the effect of treatment with L-N-(1-iminoethyl)lysine (L-NIL), a selective inhibitor of the cytokine-inducible isoform of NOS, on the clinical course of active and adoptive EAE in Lewis rats. We find that while L-NIL trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 32 publications
6
38
0
Order By: Relevance
“…Its inhibition leads to a more severe disease in a primary course of EAE (17,18,32,33), and as we have now shown, its inhibition can initiate a second episode of inflammatory cell accumulation in the CNS. In contrast, it appears as if the production of NO in the CNS, in excess of normal levels, is required for clinical expression of disease.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Its inhibition leads to a more severe disease in a primary course of EAE (17,18,32,33), and as we have now shown, its inhibition can initiate a second episode of inflammatory cell accumulation in the CNS. In contrast, it appears as if the production of NO in the CNS, in excess of normal levels, is required for clinical expression of disease.…”
Section: Discussionsupporting
confidence: 56%
“…The difference between their findings and ours could of course be due to the fact that L-NIL is more specific for iNOS than is L-NMA; the latter also inhibits the endothelial (eNOS) and neuronal (nNOS) enzymes. Dose and timing of treatment could also account for the different results, and most importantly, based on the findings presented in this work, we would now suggest that unless Gold et al (32) had ceased L-NIL treatment before termination of the experiment, clinical disease would not have been seen. We have shown in this work the necessity for cessation of inhibitor treatment in order for clinical disease to occur (Fig.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Despite extensive knowledge about NO regulation, the role of NO in tissue inflammation is controversial, as illustrated by studies involving the animal model for multiple sclerosis, experimental allergic encephalomyelitis (EAE). Some investigators concluded that NO is involved in the pathogenesis of EAE (4 -12), while others reported protective effects of NO (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Although epitope spreading is hypothesized to be responsible for relapses (3)(4)(5)(6), the factors involved in recovery from the disease phases have been difficult to define. Mechanisms thought to play a role in recovery include apoptosis of effector T cells in the CNS, suppressive cytokines, immune deviation, and NK cells (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Regulation Of Experimental Autoimmune Encephalomyelitis Inmentioning
confidence: 99%